PENINGKATAN KEPEMIMPINAN INOVASI DALAM TRANSFORMASI TEKNOLOGI - Kosasih Kosasih; Zulfa Fitri Ikatrinasari (Media Resonansi Pengabdian Masyarakat, 2025)
This community engagement initiative was designed to strengthen innovation leadership capacity within a manufacturing enterprise undergoing digital transformation. The program targeted three primary challenges: organizational resistance to change, inadequate decision-making capabilities among mid-level leaders regarding technology adoption, and the underdevelopment of human resource practices aligned with innovation goals. The intervention was structured in four progressive stages: an initial needs assessment, a two-day experiential workshop, a one-week field-based mentoring process, and a post-program evaluation employing both pre-post testing and observational methods. The workshop emphasized digital mindset development, design thinking methodologies, and transformative leadership, all delivered using experiential and peer-assisted learning strategies. Post-intervention analysis revealed a marked improvement in innovation literacy among participants, with comprehension scores rising from 60% to 85%. Additionally, five supervisory teams successfully piloted basic digital tools—such as production monitoring dashboards and digital shift-scheduling systems—resulting in measurable improvements, including a 15% reduction in material waiting time and heightened employee participation in daily innovation forums. The initiative also fostered the emergence of internal innovation champions, thereby promoting sustained organizational change. These outcomes highlight the efficacy of practice-oriented capacity-building programs in enhancing organizational adaptability and digital readiness in the manufacturing sector.Keywords: innovation leadership, digital transformation, experiential learning, manufacturing industry, community engagement.